The Influence of Creativity and Product Innovation on MSME’s Business Sustainability: A Qualitative Study on Ummina Halal Food Bekasi - Umi Maghfiroh; Nanang Setiawan (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to explore the impact of creativity and product innovation on business sustainability. It employs a descriptive qualitative method, focusing on the MSME Ummina Halal Food Bekasi. The research findings indicate that creativity and product innovation significantly influence the sustainability of Ummina Halal Food Bekasi. There has been a significant improvement in product sales and revenue following the creative and innovative launch of new products by Ummina Halal Food. The business of Ummina Halal Food has been well received by the local community, positively affecting the company's reputation, and customers are very enthusiastic about the product developments at Ummina Halal Food. Creativity and product innovation have a positive impact on business sustainability in the entrepreneurial context, leading to increased profitability for SMEs. This research contributes to theoretical development by enriching the literature on the role of creativity and innovation in business sustainability, especially in the context of MSMEs. Practically, this study provides insights for MSME entrepreneurs on the importance of innovation and product creativity in enhancing their business profitability and reputation